«Studying up» im Schweizer Justizvollzug? : Reflexionen und Perspektiven aus der empirischen Forschung - Wyssling, Jago; Frey, Louise (Über Mauern blicken - 25 Jahre Forschen im Justizvollzug: Festschrift für Ueli Hostettler zum 65. Geburtstag, 2025)
In “Up the Anthropologist – Perspectives Gained from Studying Up,” US anthropologist Laura Nader (1972) argued that research should focus on areas where formal decision-making power, responsibility, and influence are visible. She argued that this perspective allows for a critical examination of the negotiation and maintenance of power relations and (supposed) social givens. This article proposes to transfer this research paradigm to the Swiss prison system and to take a look “upwards” at those institutions in Switzerland that are dedicated to the execution of sentences as a legal mandate. To this end, theoretical and empirical perspectives are developed and then supplemented with reflections on experiences from two anthropological research projects conducted in connection with the Prison Research Group led by Ueli Hostettler. An exploratory look at the position of prison directors is used as an example: the ethnographic material reveals how directors navigate between numerous and sometimes contradictory logics that are applied in the Swiss prison system. These contradictory logics pose a challenge, but at the same time they become a resource, as they create discretionary leeway for the actors. By highlighting this scope for action and discretion, the authors argue for greater research interest and public awareness of leadership positions and decision-making power in everyday prison life. (machine translation)